Response of the 30MHz and the fluxgate magnetometer at Maitri to onset of geomagnetic disturbance - Elango, P.; Bist, S.S.; Meshram, D.K.; Rajaram, G. (My University, 2000)
An attempt has been made to understand the physical processes in the auroral ionosphere over MAITRI (geog. coord. 70.75o S, 52.8°E) and their response to geomagnetic disturbances. After observing the signatures of auroral ionospheric current systems on the ground magnetograms of fluxgate magnetometer, we tried to correlate these with the auroral absorption events recorded by a 30 MHz Riometer. The radio noise absorption is caused by the charged, particle precipitation in the auroral ionosphere i.e. by the secondary ionisation created in the lower ionosphere over Maitri. While passing through the region of enhanced electron density the cosmic radio noise suffers increased absorption resulting in a decrease in signal strength received by Riometer on the ground absorption events are categorized into the dawn, daytime, dusk and nighttime events and corresponding variations in the ionospheric current systems are presented here. The X, Y and Z variations recorded by the magnetometer give clues to the direction, intensity and extent of overhead auroral currents systems.
Keywords: Dusks; Geomagnetic disturbance; Fluxgate magnetometer; Auroral ionospheric current systems; Maitri